Radiation exposure to surgeon during selected orthopaedic procedures under fluoroscopic guidance technique - Budin, Tengku Muzaffar Tengku Mohamed Shiha (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2018)
The number of orthopaedic surgical procedures using image intensification fluoroscopic assistance had increased markedly over the past few years. There are growing concerns over possible associated radiation health hazards. In this study, scattered radiation to the eye, hand and neck of the primary surgeon were measured during interlocking nail of femur and dynamic hip screw fixation assisted by the fluoroscopic machine. Thennoluminescent dosimeter was used to quantify the radiation dose received by the surgeon. Mean radiation exposure time or duration that fluoroscopy was used during the procedure for interlocking nail of femur and dynamic hip screw fJXation were 3.89 minutes and 3.03 minutes respectively. Study showed that the primary surgeon received certain amount of scattered radiation dose during the procedures. The hand received the highest scattered dose followed by the eye and neck. The scattered dose was small. By extrapolating these results, it is unlikely for an individual surgeon to receive more than the recommended annual dose limit as set by the international organization.